2002
DOI: 10.1016/s1097-2765(02)00513-0
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast CDK Inhibitor Sic1 Prevents Genomic Instability by Promoting Replication Origin Licensing in Late G1

Abstract: G(1) cell cycle regulators are often mutated in cancer, but how this causes genomic instability is unclear. Here we show that yeast lacking the CDK inhibitor Sic1 initiate DNA replication from fewer origins, have an extended S phase, and inefficiently separate sister chromatids during anaphase. This leads to double-strand breaks (DSBs) in a fraction of sic1 cells as evidenced by the accumulation of Ddc1 foci and a 575-fold increase in gross chromosomal rearrangements. Both S and M phase defects are rescued by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
231
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(258 citation statements)
references
References 59 publications
24
231
3
Order By: Relevance
“…Similar precocious S-phase defects linked to DNA damage and chromosomal instability have been observed in sic1 mutants as well as in cells overexpressing members of the Swi/Snf family of transcription factors (Lengronne and Schwob, 2002;Sidorova and Breeden, 2002). To address this possibility, we generated a dia2 clb5 clb6 triple deletion mutant.…”
Section: Delaying S-phase Entry Alleviates S-phase Dna Damage In Dia2mentioning
confidence: 55%
“…Similar precocious S-phase defects linked to DNA damage and chromosomal instability have been observed in sic1 mutants as well as in cells overexpressing members of the Swi/Snf family of transcription factors (Lengronne and Schwob, 2002;Sidorova and Breeden, 2002). To address this possibility, we generated a dia2 clb5 clb6 triple deletion mutant.…”
Section: Delaying S-phase Entry Alleviates S-phase Dna Damage In Dia2mentioning
confidence: 55%
“…This value is significantly larger than the 35-kb interorigin distance estimated earlier from 2D gel and microarray-based analyses (Newlon and Theis 1993;Raghuraman et al 2001), supporting the view that only a fraction of the replication origins fire in a given cell. These authors were also able to reveal subtle initiation defects in cells defective for the CDK inhibitor Sic1, which were hardly detectable with classical biochemical assays (Lengronne and Schwob 2002). Stronger initiation defects were also measured in various initiation mutants using this approach (Devault et al 2002;Semple et al 2006;Shimada et al 2002).…”
Section: Single-molecule Analysis Of Dna Replication Profilesmentioning
confidence: 93%
“…3a, interorigin distances (IODs) are influenced by the overall length of analyzed DNA fibers. In initial DNA combing experiments, fiber lengths could not be determined for technical reasons, and IODs were essentially measured within clusters of early origins (Lengronne et al 2001;Lengronne and Schwob 2002;Shimada et al 2002). With the development of single-stranded DNA (ssDNA) staining procedures, BrdU tracks could be assigned to the same fiber over much longer distances, revealing the presence of large repressed domains in between clusters of active origins (Tourriere et al 2005).…”
Section: Single-molecule Analysis: Lessons From Yeastmentioning
confidence: 99%
“…Several studies using this approach have demonstrated that there are eight pathways for suppressing these chromosomal aberrations, while six pathways promote GCR formation. The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%